Knots and Holes: An Essay Film on the Life of Nets - Van de Port, Mattijs (Journal of Anthropological Films, 2024)
Nets are all around us. They materialize such principles as connecting, filtering and patterning. Which is why we might want to have a closer look at what people do with them – and what they do with people. In Bahia, Brazil, I travelled to places where people work with nets. I recorded the conversations, emotions and sensations that occur in the presence of nets. I went on a fishing trip with Tico. I spoke with evangelicals, who sought to explain the biblical parable of the fishing net. I hung out with the boys from the Candomblé religion, who have their shirts made of lace. And I never stopped wondering how the principles of filtering and patterning play themselves out in my own life - as a filmmaker, as an anthropologist, as a-gay-man-in-love. Keeping alive the tension between openness and closure, knot and hole, grasping and caressing, this film invites its audiences to ponder the observation that all we humans ever do is to impose structures onto life and being, then to find out that neither life, nor being, follow our designs.